1976
DOI: 10.1007/bf00582874
|View full text |Cite
|
Sign up to set email alerts
|

Recombination between mutants ofPhycomyces with abnormal phototropism

Abstract: Sexual crosses were studied between mutants of Phycomyces blakesleeanus with abnormal phototropism (phenotype mad). Recombination frequencies were determined among five genes madA to madE. No clear evidence was found for linkage between any of the genes. Inconsistent results in crosses involving madC are attributed to nonisogenicity between the particular strains used. One mad strain was discovered to be a double mutant. A new gene, tentatively designated madG, was segregated from a cross involving that strain. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Prior to a sexual analysis it was necessary to isolate mutants in similar genes in a (+) mating type. The first sexual crosses were reported by ESLAVA et al (1976). Whereas heterokaryon formation requires extreme dexterity, the sexual cycle is time-consuming.…”
Section: Phycomycesmentioning
confidence: 97%
See 1 more Smart Citation
“…Prior to a sexual analysis it was necessary to isolate mutants in similar genes in a (+) mating type. The first sexual crosses were reported by ESLAVA et al (1976). Whereas heterokaryon formation requires extreme dexterity, the sexual cycle is time-consuming.…”
Section: Phycomycesmentioning
confidence: 97%
“…They are affected only in phototropism and can be stimulated to bend by exceedingly high light intensities. By using sexual crosses it was possible to further ascertain that the seven complementation groups represent seven different genes, all unlinked (ESLAVA et al 1976. Using these techniques it was possible to construct a family of 21 double mad mutants and one triple mutant mad A, B, C .…”
Section: Phycomycesmentioning
confidence: 99%
“…Upon illumination with blue light, the mycelium responds by increased synthesis of p-carotene and increased initiation of sporangiophores (5,11,13,17,18). Extensive genetic analyses have shown that at least eight complementation groups (madA through madH) are involved in the action network that controls the sensory responses of P. blakesleeanus (5,10,16,24). Recently, a transformation system for Phycomyces spp., based on the expression of the transposon Tn903-derived kanamycin resistance gene, has been established (26).…”
mentioning
confidence: 99%
“…Whatever the mechanism(s) of recombination in the zygospore, individual genes could then be defined into complementation groups and their relative placement on chromosomes established through genetic linkage analysis. Over a two decade period this process led to the measurement of linkage distances based on segregation between these markers [20], [21], [22], [23], [24], [25], [26], including centromeres that were mapped with the equivalent of tetrad analysis [27], [28]. The first genetic map was reported in 1987 [28], and the updated map was published in 1996 [29].…”
Section: Introductionmentioning
confidence: 99%